Massage Teknik Effuage,Tekanan Darah, Hipertensi, Lansia - redho, ahmad; Isni Yuli Lestari, Tengku; Safitri, Nurul (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Hypertension in the elderly is high blood pressure with a medical condition where blood pressure increases above normal, namely 140/90 mmHg which is at risk of morbidity and mortality. The purpose of this study was to determine the effect of effluage technique massage on reducing blood pressure in the elderly with hypertension in Rejosari Village RT.001 RW.003. This type of quantitative research with the method of pre-experimental design one group pretest-posttest. The research sample was determined by purposive sampling technique and obtained a sample of 55 people. Statistical test using the Wilcoxon signed rank test. The results of the study found that before the intervention was given the average MAP value was 133 mmHg and after the intervention was given, the average MAP value was 120 mmHg with a Pvalue of 0.000, because the Pvalue <0.05 means that there is an effect of Effluage Massage Techniques on Reducing Blood Pressure in Elderly With Hypertension. In reducing blood pressure, non-pharmacological therapy can be done, one of which is relaxation therapy, massage with the effleurage technique, which is useful for reducing peripheral resistance and increasing the elasticity of blood vessels. There is a need for health education for people with hypertension to take advantage of massage effleurage relaxation therapy as an alternative therapy that can be used to control blood pressure so that it is within normal limits.